2020
DOI: 10.1590/1982-4327e3038
|View full text |Cite
|
Sign up to set email alerts
|

Academic Procrastination: Relationships with Support from the Environment and Self-Leadership

Abstract: Procrastination is the behavior related to voluntary delays at the beginning or end of tasks and in decision making. The aim of this study was to evaluate the mediational effect of self-leadership strategies on the relationship between academic procrastination and support from the environment. A cross-sectional correlational study was carried out with the participation of 1,436 students. Three instruments were used: Learning Support Scale, Academic Procrastination Scale - Short Form and Revised Self-Leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Their results showed that academic procrastination negatively predicted subjective well-being and positively predicted satisfaction with a postgraduate program. In another research study in Brazil with university students, Melo and Mendonça (2020) assessed the mediating role of self-leadership strategies in the relation between academic procrastination and environment support. Their results corroborated their hypothesis that self-leadership strategies reduce procrastination levels and the influence of environmental support.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that academic procrastination negatively predicted subjective well-being and positively predicted satisfaction with a postgraduate program. In another research study in Brazil with university students, Melo and Mendonça (2020) assessed the mediating role of self-leadership strategies in the relation between academic procrastination and environment support. Their results corroborated their hypothesis that self-leadership strategies reduce procrastination levels and the influence of environmental support.…”
Section: Introductionmentioning
confidence: 99%